COVID-19 Vaccine Anaphylaxis: Current Evidence and Future Approaches - Laisuan, Wannada (Frontiers in Allergy, 2021)
Vaccine anaphylaxis is rare; however, severe allergic reactions after administration of a coronavirus disease 2019 (COVID-19) vaccines have been reported. Excipients in the vaccine may play a role in severe allergic reactions post-vaccination. Various mechanisms, including IgE-mediated pathways, direct mass cell stimulation via the Mas-related G protein-coupled receptor-X2, and complement pathway activation, have been proposed to cause the anaphylaxis. Skin testing, using the basophil activation test, has been used to clarify the mechanism of the anaphylaxis and provide safety information for the next injection. Here, we review the current evidence and suggested approaches for patients who experienced an immediate severe allergic reaction to the first dose of a COVID-19 vaccine.